6 - Crise économique et financière - austérite et FMI : Le cas du Maroc - Habib El MALKI (Africa Development, 1985)
The financial crisis is a major phenomenon of the eighties. Moroc co among other African countries is affected by it. In this article, the follo wing issues are studied: 1. The causes of the situation, especially in Morocco. Two kinds of factors are to be taken into account: external factors: International monetary and financial chaos, the neo-protectionist attitude of advanced capitalist countries particularly of the E.E.C. (European Economic Community); internal factors, related to the prevailing economic strategy and to the management of the financial and economic policy. The combined effect of such factors can be measured by the external unbalances, and a greater deficit in public finances. 2. The financial crisis paved the way for the interventionist poli cy of the IMF which, in spite of specific and different national conditions, gives the same answer through its «adjustment programme». The IMF with its highly keynesian diagnosis and therapy advocates a <rregulation policy» of drastic cuts in private and public con sumption. To this effect, the Fund insists on a liberalization of the eco nomy and of the exchanges. In other words, a restoration of the macro economic balances by and through the market.